Validation of a simple ECG score for infarct size estimation in patients with first-time ST-elevation myocardial infarction. (8th February 2021) - Tiller, C; Reindl, M; Holzknecht, M; Lechner, I; Kalles, V; Rangger, A; Mayr, A; Klug, G; Brenner, C; Bauer, A; Reinstadler, S; Metzler, B
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Austrian Science Fund Background: The magnitude of myocardial damage after acute ST-elevation myocardial infarction (STEMI) is a crucial prognostic determinant. Cardiac magnetic resonance (CMR) imaging offers a precise infarct severity assessment after STEMI; however, limited to restricted availability in daily clinical routine. Recently, a simple ECG score (DETERMINE score) was developed for infarct size (IS) estimation in STEMI patients with prior infarction. We sought to validate this score in patients with first-time STEMI for the assessment of myocardial injury visualized by CMR. Methods: In this validation study, 423 revascularized first-time STEMI patients (median age 56, 17% women) were included. ECG was conducted at discharge for evaluation of the DETERMINE and Selvester score. CMR imaging was performed at a median of 3 days for the assessment of infarct characteristics (IS and microvascular obstruction [MVO]). Results: Median DETERMINE score of the overall cohort was 8 points (interquartile range: 5-11). Patients presenting with a score > 8 points had more often anterior infarct localization (64% vs. 29%, p < 0.001) and higher peak hs-TnT levels (6957 ng/l vs. 3117 ng/l, p < 0.001). In linear and binary multivariable logistic regression analysis, the DETERMINE score remained as independent associate of IS (odds ratio [OR]: 1.09, 95% confidence interval [CI] 1.00 to 1.18, p = 0.047) and MVO (OR: 1.09, 95% CI 1.02 to 1.16, p = 0.016), after adjustment for Selvester score and peak hs-cTnT. Conclusions: In survivors of first-time STEMI, the DETERMINE score provides an easy and inexpensive tool for suitable IS estimation. Moreover, the DETERMINE score showed significant and independent association with MVO. Thus, this simple ECG score might help identify patients at high risk of large infarct burden who might benefit from more aggressive treatment strategies.